DOI: 10.1016/s0742-6186(06)15010-6
|View full text |Cite
|
Sign up to set email alerts
|

Pay for Performance Where Output is Hard to Measure: The Case of Performance Pay for School Teachers

Abstract: The introduction of performance-related pay with Performance Management in the state school sector of England and Wales represents a considerable change in the school management system. After 2000, all teachers were subject to annual goal setting performance reviews. Experienced teachers were offered an extended pay scale based on performance instead of seniority, and to gain access to the new upper pay scale, teachers had to go through a 'threshold assessment' based on their professional skills and performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…This explains evidence suggesting that in spite of more sophisticated tools for output measurement performance has not improved (e.g. Marsden & Belfield, 2006).…”
Section: Output Controlmentioning
confidence: 99%
“…This explains evidence suggesting that in spite of more sophisticated tools for output measurement performance has not improved (e.g. Marsden & Belfield, 2006).…”
Section: Output Controlmentioning
confidence: 99%
“…In contrast, approaching the process from the point of view of integrative bargaining, one would look for evidence of steps to reconcile differences in priorities between classroom and head teachers and signs of a process of compromise. This appears to have happened in a significant number of schools, between a quarter and a third, which have successfully implemented the new system of performance management for schools (see Marsden and Belfield, 2006). The negotiation of change in the teachers' zone of acceptance in these schools is explained below using a simple diagrammatic presentation of some of the options and how the compromise could be reached.…”
Section: Educationmentioning
confidence: 99%
“…Similarly, if the school could provide extra support and professional development, then teachers may be able to teach both elements more effectively. Marsden and Belfield (2006) found that many schools used performance management in order to identify organisational support that could be given to teachers, such as easing difficult workloads, providing professional development, and addressing morale problems. For simplicity, the right hand panel focuses simply on the release of teaching time from other activities in order to respect classroom teachers' views on balance, and the head teacher's need for improved attainments.…”
Section: Insert Figurementioning
confidence: 99%
See 2 more Smart Citations